The many faces of the superworld : (World Scientific, 2000)
This book is a compilation of the original papers and review articles, devoted to various aspects of supersymmetry, written by the outstanding researchers in the field, theorists whose work shaped the present day theory and continues to make a profound impact on the frontier directions of development. A wide range of topics is discussed -from subtle results in the superstring theory to supersymmetry-based phenomenology. Most of the articles have been prepared specifically for this volume.